ANXIETY AND INTERVENTION IN SPORT - Olivia Andiana (Ordik, 2010)
Anxiety, stress and worry about the athletic experience on the part of athletes is a major area of concern. It is estimated that many young athletes drop out of organized sport each year due to frustration and fear of failure. Many young athletes thrive on the pressure and tension association with competitive sport. However, far too many find that the experience precipitates feelings of apprehension and stress. In this article I discuss the phenomenon of anxiety and how it affects the athletic experience. I present numerous strategies designed to intervene and reverse the negative effects of anxiety on the athlete. To a large extent, intervention strategies are used to counter the effects of runaway anxiety and associated arousal. However, it is also important to realize that psychological intervention strategies can also be used to motivate and increase the attentional readiness of the athlete.